Analisis Kinerja Penyearah Terkontrol Gelombang Penuh Tiga Fasa Menggunakan Thyristor Berbasis Simulasi MATLAB/Simulink - Tika Juni Lestari; Ridho Syahban; Aditya Utama (Kampus Akademik Publiser, 2026)
This study investigates the performance of a three-phase full-wave controlled rectifier using thyristors, focusing on the influence of firing angle on output voltage and current stability. The simulation was conducted using MATLAB/Simulink, with measurement blocks to observe three-phase input and output waveforms. The results show that the rectifier provides a stable DC output with minimal ripple, and the firing angle effectively controls the average output voltage. Input voltage and current remain balanced, with RMS and standard deviation values indicating consistent system behavior. These findings demonstrate the suitability of controlled three-phase rectifiers for industrial applications requiring reliable DC power conversion, and provide insight for optimizing thyristor triggering in practical systems.